CHARACTERISTICS OF HABITAT AND BIVALVE DENSITY IN INTERTIDAL ZONE OF SUNGAI CINGAM VILLAGE OF RUPAT SUB DISTRICT OF BENGKALIS REGENCY OF RIAU PROVINCE - Nadratul Jamila; Syafruddin Nasution; Efriyeldi Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTBivalves are biota that live in the bottomof waters that can be used as bioindicators to predict water quality. This research was conducted in March-April 2018 which is located in intertidal zone of Sungai Cingam Village of Rupat Sub-district. Thisresearch aims to know the characteristics of habitat, species and density bivalvia. The method used in this research was survey method and determination of sampling location by purposive sampling. Measurement of water quality parameters was done in situ ie temperature, salinity and pH. Substrate type there are2 types of muddy sand and sandy mud. Organic matter is very low and very high. Suspended solids are low and high. Water quality parameters are still favorable for the life aquaticorganisms. Type of bivalves found there are 5 species of Meretrix meretrix, Polymesoda expasa, Pharella acutidens, Pilsbryoconcha exilis, Corbicula javanica. The highest density is at station 3 that is 5.89 ind/m2. The lowest density is at station 1 that is 4.89 ind/m2.Keywords: Habitat Characteristics, Species, Density, Bivalves.